Polymerase Chain Reaction (PCR) - Rahimee, Israrullah; Azeemi, Mohammad Azeem (International Journal For Research In Biology & Pharmacy, 2020)
Polymerase chain reaction (PCR) is popular widely used methods which makes millions to billion copies of a specific D N A molecules helping scientists to take small sample of D N A And amplify it to an enough amount to study it in details. This method was invented 1984 by the American biochemist Kary Mullis at Cetus corporation. Polymerase chain reaction is very sensitive and specific test used as diagnostic test for different purpose.it is highly specific and and rapid diagnostic test for different infectious disease such as mycobacterium tuberculosis, an aerobic bacteria, human immune deficiency virus (H I V), corona virus (COVID-19), Pertussis (whooping cough), rapid and accurate diagnosis of anthrax specially in case of bioterrorism, salmonella, Malaria, Helicobacter pylori infection. Polymerase chain reaction is also used for diagnosis of cancers specially lymphoma and leukemia. It is also used broadly in research and forensic medicines. According to the importance of polymerase chain reaction in diagnosis of infectious and noninfectious disease we have reviewed principle, procedure, Medical application, strong point (Advantages) and negative point (disadvantages) of polymerase chain reaction.